2017
DOI: 10.1111/ijfs.13507
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the structure, digestibility and immunoreactivities of glycinin induced by the cross‐linking of microbial transglutaminase following heat denaturation

Abstract: Summary This study aimed to evaluate the effects of microbial transglutaminase (MTG)‐mediated modification on the structure, digestibility and immunoreactivities of glycinin. Glycinin was separated from soya bean and cross‐linked with MTG, and the sulphate‐polyacrylamide gel electrophoresis (SDS‐PAGE) showed that the molecular weight of cross‐linked glycinin was higher than that of native glycinin. Individual MTG cross‐linking could maintain stable secondary structures and spatial structure. Sequential heat de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
(42 reference statements)
3
11
0
Order By: Relevance
“…The IgG‐ and IgE‐binding capacity of SM and FSM proteins were assessed through competitive inhibition ELISA, as previously reported, with few modifications . In brief, the native SM protein was coated (2 and 10 μg/mL for IgG and IgE tests, respectively, 100 μL per well) in carbonate buffer overnight at 4 °C.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…The IgG‐ and IgE‐binding capacity of SM and FSM proteins were assessed through competitive inhibition ELISA, as previously reported, with few modifications . In brief, the native SM protein was coated (2 and 10 μg/mL for IgG and IgE tests, respectively, 100 μL per well) in carbonate buffer overnight at 4 °C.…”
Section: Methodssupporting
confidence: 72%
“…The IgG-and IgE-binding capacity of SM and FSM proteins were assessed through competitive inhibition ELISA, as previously reported, with few modifications. 19 In brief, the native SM protein was coated (2 and 10 μg/mL for IgG and IgE tests, respectively, 100 μL per well) in carbonate buffer overnight at 4 ∘ C. For the competitive proteins, 60 μL/well of samples (1, 2, 5, 10, and 20 μg/mL for IgG-binding; 20, 40, 80, 160, and 320 μg/mL for IgE-binding) was mixed with 60 μL/well of rabbit anti-soybean sera (diluted 1:5000, for IgG binding test) or soybean-allergic patients' serum pool (diluted 1:10, for IgE binding test). For the IgE binding test, HRP-conjugated streptavidin (diluted 1:60) was also added.…”
Section: Elisamentioning
confidence: 99%
“…Glycinin extraction was conducted following a previous protocol [ 12 ]. All centrifugation was performed at 10,000× g , 4 °C for 15 min in a centrifuge (TGL-16R, Shan Dong BaiO Medical Technology CO., LTD., Shandong, China).…”
Section: Methodsmentioning
confidence: 99%
“…Several technologies have been developed to reduce the antigenicity of soy proteins, including thermal and non-thermal processing (e.g., high hydrostatic pressure treatment, enzymatic hydrolysis, genetic modification and microbial fermentation) [ 3 , 11 , 12 , 13 , 14 ]. Fermentation, an ancient processing approach, demonstrated improvements in the functional and nutritional properties of soy products [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results inferred that alkaline pH shifting in conjunction with TG crosslinking can be an effective way to diminish the IgE-binding of glycinin. Yang et al (2017) observed that sequential heat treatment and enzymatic crosslinking unfolded the structure of glycinin and reduced the digestion stability. Bai et al (2020) evaluated the sensitization effect of crosslinked tofu with microbial TG in a BALB/c mouse model.…”
Section: Soybean Allergymentioning
confidence: 99%